Prodromus of a fern flora for Bolivia. XXXIX. Oleandraceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis to the family Oleandraceae in Bolivia, including three species in the single genus Oleandra. Despite the low number of species, the taxonomy of these is not fully resolved and calls for further study.